Análise do impacto de atividades externas de lazer na vida dos residentes de uma instituição de longa permanência: o caso do Lar dos Idosos Nossa Senhora da Saúde - Silva, Ana Carolina Lopez (2010)
This work aims at studying the impact of outdoors leisure activities on the life of the residents at the Elderly Nursing Home Nossa Senhora da Saúde, located in the municipality of Belo Horizonte. Based on what the residents said, there was an attempt to identify elements which could contribute to the reflection and the debate about leisure in the life of the elderly. The issue of outdoors leisure of elderly people was proposed to be thought per category of analysis as established by the literature, such as: concept of elderly, long term care institution and leisure. Two outdoors rides were performed with the residents to the Zoo and to the Museum of Arts and Trades, so that they could experience a leisure activity outside the Home. Afterwards, six interviews were conducted with the residents (three men and three women) in order to assess the impact of the outdoors leisure activities. The lack of knowledge of the elderly who were studied in relation to the issue could be observed. In the interviews, it could be verified that there was a lack of experience in terms of leisure activities through life and an attitude of passivity and renouncement of life in some of the elderly. It could also be verified that the outdoors rides brought new experiences. Therefore, it is necessary to promote more awareness about leisure in this age group, demonstrating its benefits and the various manners to experience it. This will contribute to the search for new alternatives, causing these people to escape from the routine of their homes to make their lives more pleasant